MYC and BCL2 overexpression is associated with a higher class of Memorial Sloan-Kettering Cancer Center prognostic model and poor clinical outcome in primary diffuse large B-cell lymphoma of the central nervous system. Issue 1 (December 2016) - Kim, Sehui; Nam, Soo; Kwon, Dohee; Kim, Hannah; Lee, Eunyoung; Kim, Tae; Heo, Dae; Park, Sung; Kim, Chul; Jeon, Yoon
Abstract Background Primary diffuse large B-cell lymphoma of the central nervous system (PCNS-DLBCL) is a distinct clinicopathological entity with a poor prognosis. Concurrent MYC and BCL2 overexpression predicts inferior prognosis in systemic DLBCLs. However, the prognostic significance of MYC and BCL2 in PCNS-DLBCL remains elusive. Methods Immunohistochemistry (IHC) of MYC, BCL2 and BCL6 was performed on tumor samples from 114 patients with PCNS-DLBCL. IHC score was assigned based on the proportion of immunostained cells. Results MYC, BCL2, and BCL6 IHC scores were 18.16 ± 19.58, 58.86 ± 35.07, and 39.39 ± 37.66 % (mean ± SD), respectively. Twenty-one cases (18.1 %) were designated as MYC-positive with a cutoff score of 40. BCL2 positivity was found in 87 cases (75.0 %) using a cutoff score of 30. MSKCC (Memorial Sloan-Kettering Cancer Center prognostic model) class 2 and 3 had higher rates of MYC and/or BCL2 positivity (MYC, P  = 0.012; BCL2, P  = 0.008; dual-positive, P  = 0.022). Poor KPS (Karnofsky Performance Status score <70), multifocal disease, Nottingham-Barcelona score ≥2, and MSKCC class 2 and 3 were related to shorter progression-free survival (PFS) (P  = 0.001, 0.037, 0.001, and 0.008, respectively). Patients with older age (>60 years) showed poorer overall survival (OS) (P  = 0.020). MYC positivity was associated with poor PFS (P  = 0.027), while patients with BCL2 positivity exhibited a shorter OS (P  = 0.010). Concomitant MYC and BCL2 positivity was related to poor PFS (P  = 0.041), while the lack of both MYC and BCL2 expression was related to prolonged OS (P  = 0.014). MYC and BCL2 expression had no independent prognostic implication by multivariate analysis in overall patients with PCNS-DLBCL. However, among patients treated with combined high-dose methotrexate, vincristine and procarbazine and radiotherapy, dual MYC and BCL2 overexpression (a cutoff score of 60) was an independent poor prognostic indicator (P  = 0.010). Conclusions Evaluation of MYC and BCL2 expression may be helpful for the determination of PCNS-DLBCL prognosis.